2023
DOI: 10.1111/jcal.12802
|View full text |Cite
|
Sign up to set email alerts
|

Students' expectations of Learning Analytics across Europe

Abstract: Background Learning Analytics (LA) is an emerging field concerned with measuring, collecting, and analysing data about learners and their contexts to gain insights into learning processes. As the technology of Learning Analytics is evolving, many systems are being implemented. In this context, it is essential to understand stakeholders' expectations of LA across Higher Education Institutions (HEIs) for large‐scale implementations that take their needs into account. Objectives This study aims to contribute to k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Best efforts in broad-based developments may still run into existing barriers, such as amid countries within Europe, where developed national policies, infrastructures, and competence centers have not led to national adoption or strategies at the European level [8] . It was also found that AI and LA research at university or national levels are still predominantly overlooked, face challenges more similar than anticipated [9] , and therefore more focus can be given from national bodies and funding agencies to bridge theory-practice divides.…”
Section: Existing E Orts Around the Worldmentioning
confidence: 99%
“…Best efforts in broad-based developments may still run into existing barriers, such as amid countries within Europe, where developed national policies, infrastructures, and competence centers have not led to national adoption or strategies at the European level [8] . It was also found that AI and LA research at university or national levels are still predominantly overlooked, face challenges more similar than anticipated [9] , and therefore more focus can be given from national bodies and funding agencies to bridge theory-practice divides.…”
Section: Existing E Orts Around the Worldmentioning
confidence: 99%
“…At the same time, students can preserve their privilege to study in their place, at their own pace, without having to be physically present on a campus. Empirical findings from a trans-European study [13] indicate a high demand for LA and a certain lack of confidence in meeting the high expectations that the educational community has set for the benefits that LA can offer. The process of capturing complex students' interactions in an educational environment is far from simple.…”
mentioning
confidence: 99%